Case Report: A case of IgD lambda/lambda Multiple Myeloma in patient with acute renal failure and without monoclonal spike in serum electrophoresis - Troiano, Teresa; Brescia, Vincenzo; De Marinis, Lucia; Marinaccio, Anna; Lovero, Roberto; Rizzi, Rita; Di Serio, Francesca (Frontiers in Hematology, 2022)
Background: IgD Multiple Myeloma is a rare form of plasma cell dyscrasia and accounts for approximately 1-2% of all cases of Multiple Myeloma. It mainly affects young, male subjects; it is characterized by an aggressive course, a high production of Bence Jones protein, acute renal failure and an often unfortunate outcome compared to the other isotypes of MM. A distinctive feature is the lack of a monoclonal peak on serum protein electrophoresis (SPE). Case Report: a 57-year-old man with pain in his left lower limb and weight loss goes to the Emergency Department (Emergency Department). Laboratory tests performed showed normocytic normochromic anemia (Hemoglobin 9.4 g / dL), acute renal failure (s-creatinine 2.85 mg / dL, e-GFR 23 mL / min / 1.73 m². serum protein electrophoresis (SPE) detected only mild polyclonal in the gamma zone with no evidence of any monoclonal peak. Results: serum immunofixation (s-IFE) showed a monoclonal IgD λ band and a monoclonal λ band. The Free Light Chains (s-FLC) measurement showed a ratio of 0.04. The bone marrow biopsy confirmed an infiltration of> 20% of clonal plasma cells; renal biospy diagnosed "cast neprhopathy". Conclusion: IgD λ / λ Multiple Myeloma is a rare form of this disease with a poor prognosis; an early and correct laboratory diagnosis is crucial for appropriate treatment and effective monitoring in order to improve patient outcome.